Can neuroimaging be used to predict the onset of psychosis?. (December 2015) - McGuire, Philip; Sato, Joao R; Mechelli, Andrea; Jackowski, Andrea; Bressan, Rodrigo A; Zugman, Andre
Summary: The onset of psychotic disorders is preceded by a high-risk phase characterised by attenuated or brief psychotic symptoms and a marked decline in functioning. About a third of individuals presenting with these features develop a psychotic disorder within 3 years. A fundamental challenge in the clinical management of this population is that it is not possible to predict whether an individual at high risk will go on to develop psychosis on the basis of their presenting features. Consequently, preventive interventions that might reduce the risk of progression to psychosis cannot be selectively offered to those patients for whom they would be most useful. However, neuroimaging investigation suggests that the structure, function, and chemistry of the brain in high-risk individuals who become psychotic differ from those in individuals who do not become psychotic. In this Personal View, we review these findings and discuss the main challenges for translating them into clinical practice. The development of techniques that allow clinicians to tailor interventions to the level of risk is a major translational goal for research in this field.